2012
DOI: 10.1017/s0022215112001168
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the LigaSure vessel sealing system during major head and neck cancer surgery

Abstract: Our experience indicates that the surgical technique described is safe and effective. The main advantages of the LigaSure system are that it simplifies the procedure and eliminates the need for clips and suture ligations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…This likely explains why the operation duration in the current study was shorter using LigaSure‐assisted functional neck dissection. Similar results for other head and neck procedures were also reported in the literature …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This likely explains why the operation duration in the current study was shorter using LigaSure‐assisted functional neck dissection. Similar results for other head and neck procedures were also reported in the literature …”
Section: Discussionsupporting
confidence: 90%
“…It works by delivering the required amount of bipolar energy and forces to transform the collagen and elastin within the vascular walls . In addition, it was reported that the LigaSure system can safely coagulate and seal large vessels up to 7 mm in diameter . The instrument decreases the necessity for coagulation of small blood vessels and improves the surgical field, which can accelerate surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its hemostatic effect has been previously validated in thyroidectomy and head and neck cancer surgeries. 22,23 Few reports of LigaSure use in orthopaedic oncologic procedures have been described to date. Hoshi et al 8 reported its use in a case report of a debulking surgery of a huge mass of elephantiasis neuromatosa.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Fakhry et al ., published in 2012, evaluated the haemostatic efficacy of electrothermal bipolar vessel sealing in major head and neck cancer surgery, observing post-operative bleeding in 2 of 34 patients treated 23 . Nevertheless, the authors did not quantify the post-operative bleeding, nor did they compare electrothermal bipolar vessel sealing with other cut-and-seal instruments.…”
Section: Discussionmentioning
confidence: 99%